G183 Improving the patient pathway: aggregation of marginal gains in a secondary paediatric allergy service. (7th April 2014) - Eisen, S; van der Poel, L; Williams, C; Clough, L; Musial, M; Lowe, K; Walsh, O; Salt, P
Abstract : Aims: Our multidisciplinary paediatric allergy clinic often exceeded staff and session capacity, adversely impacting efficiency and patient and staff experiences. We therefore aimed to analyse and improve the 'patient pathway', from referral to treatment, of children referred to this secondary care paediatric allergy service. Methods: Data was collected over two months, using patient trackers, process templates, "waste walks" and service-user evaluation. Data was both quantitative (waiting times, staff activity, appointment duration, total clinic duration) and qualitative (patient and staff feedback). Multidisciplinary clinical and management engagement and service improvement techniques allowed fast-track changes to be implemented over the following three months. Results: During baseline data collection, 21 patients were seen per week with an average clinic visit of 2 hours. Nursing under-utilisation early in clinics was noted, leading to later "bottlenecks", and 50% of clinics overran their scheduled duration. Qualitative data from patient surveys described dissatisfaction at long waits and suboptimal provision of patient information. Fast track changes included optimisation of clinic templates enabling nurse-led investigation of follow up patients prior to clinician review, co-located clinic rooms, new patient history proforma, appropriate patient information (pre-clinic letter, web-site, leaflets, information board) and engagement of service-users ("design a logo" competition, patient focus groups, sticker charts). Analysis shows a 15% increase (3 patients per clinic) in clinic capacity, with an average 17% reduction (20 min) in visit duration. Staff activity is more evenly distributed throughout the clinic session. A reduction in clinic end times is being realised. Preliminary reports of user experiences demonstrate improvements. Ongoing data collection suggests that the improvements are sustained, and these principles have been effectively applied in other outpatient settings. Conclusions: Using multiple small changes and a multidisciplinary approach, sustained and reproducible improvements to the outpatient experience can be achieved in a short period of time and in a cost-neutral manner. Staff report enhanced morale and unexpected gains from collaboration with other stakeholders, including mutual identification of opportunities for further service improvements. Focused clinical and managerial collaboration impacts positively on outcomes.